(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
In Education, community participation is really important, therefore as many parents feel that they have to give their best for their children’s educational not only materially but also non-material support. In Madura Island, Indonesia, the condition of Islamic education institutions that are holded by Kiai Desa makes community relations with this madrasah in unique relation. Moreover, there is a tendency that the participation of rural communities in Madura is relatively greater dan broader than in cities on the island of Java. This article aims to determine: How does the community participation and the factors that encourage and inhibit community participation in Islamic religious education programs in Madura. This research is a qualitative field research witha phenomenological approach to see the existing motives of the community. The research subjects were the community of Pakaan Dajah Bangkalan and the stakeholders of Madrasah Aliyah Raudlatul Ulum Pakaan Dajah, Bangkalan. This research finds that: (1) the forms of community participation in Taman Sari and Talambak hamlets in the Islamic education program at Madrasah aliyah Raudlatul Ulum are in the form of ideas / thoughts, energy and money; (2) the driving factor for community participation in the Islamic education program at Madrasah Aliyah Raudlatul Ulum is fighting for Islam by helping the kiai’s struggle in education